A case of meningococcal meningitis with multiple cerebellar microbleeds detected by susceptibility-weighted imaging. Issue 1 (December 2015) - Miyazaki, Keita; Fukushima, Hidetada; Kogeichi, Youhei; Watanabe, Tomoo; Norimoto, Kazunobu; Taoka, Toshiaki; Okuchi, Kazuo
Abstract Background Bacterial meningitis is a fatal infectious disease of the central nervous system complicating intravascular involvements. Multiple microbleeds are rarely identified as complications because of the limited detection threshold of conventional imaging modalities. We report the first case of meningococcal meningitis with successful identification of multiple microbleeds in the cerebellum by susceptibility-weighted imaging. Case presentation A 19-year-old Japanese female was brought to our emergency department because of fever and coma. A spinal tap was performed and turbid yellow fluid was collected. A diagnosis of bacterial meningitis was established and the patient was admitted to an intensive care unit. Dexamethasone and Antibiotics were administered andNeisseria meningitides was cultured from the spinal fluid. On day 10, postcontrast magnetic resonance imaging identified enhanced subarachnoid space in the cerebellum. Susceptibility-weighted imaging showed spotty low-intensity signals in the cerebellar tissue, indicating microbleeds. The patient made a full recovery from coma and was discharged without neurological sequelae on day 24. Conclusion Meningococcal meningitis can cause multiple microbleeds in the cerebellum. In this report, we successfully identified microbleeds by susceptibility-weighed imaging. Using this imaging modality, further investigations will clarify its clinical incidence and significance.